Prikaz bolnikov z leptospirozo, zdravljenih na Oddelku za infekcijske bolezni in vročinska stanja Splošne bolnišnice Murska Sobota v letu 2002 - pomen hemokultur pri njeni diagnostiki - Pal, Emil (Zdravniški vestnik, 2003)
Background. Leptospirosis is a zoonosis with worldwide distribution. In Slovenia, Pomurje is an endemic area. Manifestations of leptospirosis may be observed as different types of disease. The range from a short-lived febrile state to a severe disease with renal failure, liver impairment, hemorrhage andfulminand course. Patients and methods. Until year 2001 in the Department of infectious diseases at General Hospital Murska Sobota, only serological methods in diagnosis of leptospirosis had been used. Only in 2002 isolation ofleptospires from blood was used. Four cases of confirmed leptospirosis hospitalized in our Department in 2002 were presented with broad spectrum of clinical courses and the significance of cultivation of leptospires from bloodin the diagnosis. Conclusions. Because of the protean manifestations of leptospirosis, microbiological tests are essential for confirmatory diagnosis.In case of epidemiological data, clinical course and laboratory markers suggesting the diagnosis of leptospirosis, it is advisible to obtain blood cultures.
Keywords: Diagnosis; diagnostika; Leptospirosis; Leptospiroza; Serodiagnosis; Weilova bolezenzoonoze; Weil'S Disease; zoonoze